Pemanfaatan Media Sosial Instagram Dalam Upaya Peningkatan Jumlah Kunjungan Wisatawan Di Pemandian Air Panas Pariban - Hia, Niscaya; Sarah, Eva Margareth; Siregar, Marupa; Cikita, Putri (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
The research was conducted at Pariban Hot Springs which is located in the village of Semangat Gunung, Karo Regency. The purpose of this research is to find out how Instagram social media is useful in efforts to increase the number of tourist visits at Pariban Hot Springs. This research is a study that uses qualitative research methods. Data sources consist of primary data and secondary data. Primary data is obtained from in-depth interviews with seven informants consisting of managers and tourists who have visited. Data collection techniques are carried out by observation, interview and documentation. The observation technique was carried out when conducting interviews with informants and observing behavior that is relevant to the theme of this research. Interview techniques in this study were structured and used interview guidelines. The results of the research obtained are the utilization of Instagram social media in an effort to increase the number of tourist visits at Pariban Hot Springs is beneficial and has a positive impact on the number of tourist visits at Pariban Hot Springs.